On the Possible Immorality of Law - Trajković, Marko; Drakić, Dragiša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
Law as such can be a source of evil. It is possible to reach this when the binding force of law is not found in moral values ​​but in sanctions. Another source of possible immorality is found in the position that the sovereign will is the law, as well as in the position "law is law". Especially dangerous is the rejection of value judgments in law, as well as moral relativism according to which everything is possible. This description of facts can be seen in authoritarian societies. Law based on the rule” law is the law” enables everything to be justified in the name of legal security, even the biggest crimes because the one who committed them only obeyed the law and obeyed its will. Thus, it is possible for the unwritten will of the sovereign to be a source of law. Such a setting of law, which is not based on values, is especially dangerous in the matter of criminal law. Efforts to explain the world of law apart from society and the world of values ​​led to a refinement of the concept of law, but at the same time it narrowed it and limited its scope of application, which caused irreversible damage. For this reason, moral values ​​are the basis of law and a barrier against its immorality. It will never happen, in the full sense, that something is in accordance with reason and contrary to moral values. On the contrary, this will strengthen the legal system, which will avoid being disarmed